The 50th anniversary of May 4, 1970 is associated with elevations of distress but no increase in mental health symptoms. (29th November 2021) - Rabinowitz, Emily P.; Sayer, MacKenzie A.; Samii, Marielle R.; Straub, Elizabeth L.; Kutash, Lindsay A.; Delahanty, Douglas L.
Abstract: Anniversaries of traumatic events are associated with increased symptoms of posttraumatic stress disorder (PTSD), depression, and anxiety, especially in individuals with prior mental health symptoms. However, research has largely focussed on 1‐year anniversaries, and it is unclear whether symptom exacerbation persists for more distal, or milestone, anniversaries. Symptoms typically decrease over time after traumatic events, but major anniversaries may be associated with increases in mental health symptoms. During and 3 months after the 50th anniversary of the political protest violence at Kent State University on May 4, 1970, 115 individuals completed measures of PTSD, depression, anxiety, and anniversary‐related stress. Participants reported greater stress ( t (97) = 4.04 p  ≤ .001) during the 50th anniversary compared to 3 months later, but there were no differences in total PTSD ( t (114) = .65, p  = .52) or depression/anxiety symptoms (all p 's > .05). Even in higher‐risk individuals (those who previously received mental health services), symptoms did not differ during versus after the anniversary. In general, long‐term anniversaries may contribute to transient increases in distress but do not induce major changes in mental health symptoms.